Dietary restriction and exercise improve airway inflammation and clinical outcomes in overweight and obese asthma: a randomized trial. Issue 1 (24th December 2012) - Scott, H. A.; Gibson, P. G.; Garg, M. L.; Pretto, J. J.; Morgan, P. J.; Callister, R.; Wood, L. G.
Summary: Background: Obesity and asthma are associated conditions; however, the mechanisms linking the two remain unclear. Few studies have examined the effects of weight loss on inflammation and clinical outcomes in obese–asthma. Objective: To compare the effects of weight loss achieved by dietary restriction, exercise or combined dietary restriction and exercise on airway inflammation and clinical outcomes in overweight and obese adults with asthma. Methods: Participants ( n = 46; 54.3% female, body mass index (mean ± SD) 33.7 ± 3.5 kg/m 2 ) were randomized to complete a 10‐week dietary, exercise or combined dietary and exercise intervention. Dual‐energy x‐ray absorptiometry was performed, the Juniper Asthma Control Questionnaire and Juniper Asthma Quality of Life Questionnaire completed and inflammatory markers, dietary intake and physical activity measured. The trial was registered with the Australian Clinical Trials Registry: ACTRN12611000235909. Results: Retention was 82.6%. Mean ± SD weight loss was 8.5 ± 4.2%, 1.8 ± 2.6% and 8.3 ± 4.9% after the dietary, exercise and combined interventions respectively. Asthma control improved after the dietary (mean ± SD; −0.6 ± 0.5, P ≤ 0.001) and combined interventions (−0.5 ± 0.7, P = 0.040), whereas quality of life improved after the dietary [median (IQR); 0.9 (0.4, 1.3), P = 0.002], exercise [0.49 (0.03, 0.78), P = 0.037] and combined [0.5 (0.1, 1.0), P = 0.007] interventions. A 5–10% weight loss resulted in clinically important improvements to asthma control in 58%, and quality of life in 83%, of subjects. Gynoid adipose tissue reduction was associated with reduced neutrophilic airway inflammation in women [β‐coefficient (95% CI); 1.75 (0.02, 3.48), P = 0.047], whereas a reduction in dietary saturated fat was associated with reduced neutrophilic airway inflammation in males ( r = 0.775, P = 0.041). The exercise intervention resulted in a significant reduction to sputum eosinophils [median (IQR); −1.3 (−2.0, −1.0)%, P = 0.028]. Conclusion and clinical relevance: This study suggests a weight‐loss goal of 5–10% be recommended to assist in the clinical management of overweight and obese adults with asthma. The obese–asthma phenotype may involve both innate and allergic inflammatory pathways.